P-Wave Visible–Shortwave–Near-Infrared (Vis-SW-NIR) Detection System for the Prediction of Soluble Solids Content and Firmness on Wax Apples. Issue 10 (October 2019) - Hua, Shih-Hao; Hsu, Hsun-Ching; Han, Pin
A nondestructive system for measuring the soluble solids content (SSC) and firmness of wax apples was developed using 670, 850, 880, 940, and 980 nm visible–shortwave–near-infrared (Vis-SW-NIR) light-emitting diode (LED) light sources and a silicon (Si) photodetector. These specified wavelengths are highly correlated with the SSC and the firmness of fruit. An LED light source was incident onto the fruit as parallel-polarized waves (P-wave) at the Brewster angle (θB ) to minimize the interfacial reflection and maximize the C–H and O–H bonds absorption signals from the fruit. Partial least squares (PLS) regression is used to build calibration modes and analyze the prediction of the correlation (r p 2 ) and the root mean square error for prediction (RMSEP) of the reflected optical signals with SSC and firmness. This resulted inr p 2 and RMSEP values of 0.87 and 0.66 °Bx, respectively, in SSC measurements and 0.80 and 1.16 N/cm 2, respectively, in firmness measurements. Therefore, the result showsr p 2 of SSC and firmness are 6.4% and 9% higher and the RMSEP are 14% and 20% lower, respectively, than those obtained using non-polarized LED light sources.